The Independence of Auditor, Corporate, Governance, Audit Quality and Audit Tenure on the Integrity of Financial Statement - Jundi Nuri Azhar (Fak. Ekonomi dan Bisnis Islam. UIN Sunan Kalijaga, 2016)
wk, 1/ nis,c.1